Water resources and reservoir engineeering proceedings of the seventh conference of the British Dam Society held at the University of Stirling, 24-27 June 1992 - Parr, Noel M.; Charles, J. Andrew; Walker, Susan, 1932- (Thomas Telford, 1992)
This volume explores the current issues and international developments in reservoir planning and operation, design and construction, monitoring and maintenance.